Binary answering machine using EEG brain signals - Chen, Wei Si. (2010)
The human brain is a highly complex and important organ that is centre of the human nervous system. The brain is also the control centre for physical movement, sleep, hunger, thirst, and virtually every other vital activity necessary to survive. The presence of electrical current in the brain was first discovered by an English physician, Richard Caton, in 1875 and Electroencephalography was later developed by a German scientist Hans Berger in 1924 to record the electrical activity of the brain. Since then, EEG had been used in researches related to the brain.